The Revised Conflict Tactics Scales (CTS2): A review of the properties, reliability, and validity of the CTS2 as a measure of partner abuse in community and clinical samples. (January 2019) - Chapman, Harriet; Gillespie, Steven M.
Abstract: The purpose of this review is to explore the Revised Conflict Tactics Scales (CTS2), focusing on its research uses for assessing Intimate Partner Violence (IPV). An overview of the CTS2 is presented, including the area that it assesses, the purpose of the tool, and its content. The tool's attempts to measure the purported construct are evaluated, drawing upon principles of reliability, validity and appropriate norms. The CTS2 has been found to be a reliable and valid instrument to measure IPV across different populations and across different cultures. However, there are some concerns regarding the internal consistency of the sexual coercion scale among female samples, and explorations of the factor structure of the CTS2 have yielded inconsistent models. While some statistical properties of the scale have been established for different populations, more research is needed to ascertain the validity and reliability of the CTS2 in varied clinical and forensic settings. The strengths and limitations of the CTS2 considered in the review have important implications for interpreting findings of studies investigating IPV using only this tool. Highlights: This paper reviews the scientific properties of the CTS2, focusing on its uses for assessing Intimate Partner Violence (IPV) The tool's attempts to measure the purported construct are evaluated, drawing upon principles of reliability, validity and appropriate norms. The CTS2 has been found to be a reliable and valid instrument to measure IPV across different population and cultures. Concerns about the reliability of the sexual coercion scale and inconsistent models of the factor structure are highlighted. Further research is needed to ascertain the validity and reliability of the CTS2 in varied clinical and forensic samples.